2014
DOI: 10.1016/j.csda.2014.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of risk measures in energy portfolios using modern copula techniques

Abstract: The present paper analyses the dependence structure between WTI and Brent crude oil spot log-returns using modern copula techniques. In a first step we apply several single equation models to the marginals to account for autocorrelation and volatility clustering. Second, to select both copulas and tail copulas characterising the joint dynamics between the time series we implement and evaluate newly introduced bootstrap-based goodness-of-fit tests. Based on each approach, a comprehensive backtesting is performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…Empirical results are provided in section 3 and section 4 concludes. ¶In this context, Jäschke (2014) proposes novel bootstrap-based goodness-of-fit tests, which help to fit the appropriate copula to the data. See also Jäschke et al (2012) for a discussion of the drawbacks of previously used goodness-of-fit test for copulas.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Empirical results are provided in section 3 and section 4 concludes. ¶In this context, Jäschke (2014) proposes novel bootstrap-based goodness-of-fit tests, which help to fit the appropriate copula to the data. See also Jäschke et al (2012) for a discussion of the drawbacks of previously used goodness-of-fit test for copulas.…”
Section: Introductionmentioning
confidence: 99%
“…§ Generally, the use of copula techniques in the context of oil prices is already established in the literature. For instance, see Jäschke (2014) for a study of the dependence structure between WTI and Brent crude oil spot log-returns using †Assuming that oil exporting countries reinvest their revenues in US dollar assets, the dollar will appreciate in the short-run. However, the long-run reaction of the US dollar against other currencies is less clear-cut and is determined by the weight of oil in US total imports compared to the US weights in OPEC imports (Coudert et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Melo Mendes and Aíube (2011) used the copula approach to model the serial dependence in financial return series. Righi and Ceretta (2011) examined the overall dependence between the U.S. and Brazilian stock markets while Aloui et al (2014), Hammoudeh et al (2014) and Jäschke (2014) have looked at cross dependencies within the energy and international stock markets.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, it has mainly been used to characterize the dependence structure among portfolio assets in both unconditional and conditional cases. For example, in the unconditional case, Jaschke [36] analyzed the dependence structure between WTI and Brent markets using different copula models. The comprehensive performance valuation on different copula-based risk estimates showed that Gumbel copula provided the best model fitting [36].…”
Section: Copula Model In the Energy Marketsmentioning
confidence: 99%
“…For example, in the unconditional case, Jaschke [36] analyzed the dependence structure between WTI and Brent markets using different copula models. The comprehensive performance valuation on different copula-based risk estimates showed that Gumbel copula provided the best model fitting [36]. Work by Anne-Laure Delatte [37] also showed that the dependence structure between the commodity and the stock markets was predominantly symmetric, as described by the Gaussian copula model [37].…”
Section: Copula Model In the Energy Marketsmentioning
confidence: 99%